Fish c-Jun N-Terminal Kinase (JNK) Pathway Is Involved in Bacterial MDP-Induced Intestinal Inflammation - Qu, Fufa; Xu, Wenqian; Deng, Zhangren; Xie, Yifang; Tang, Jianzhou; Chen, Zhiguo; Luo, Wenjie; Xiong, Ding; Zhao, Dafang; Fang, Jiamei; Zhou, Zhigang; Liu, Zhen (Frontiers in Immunology, 2020)
The c-Jun NH2-terminal kinases (JNKs) are an evolutionarily conserved family of serine/threonine protein kinases that play critical roles in the pathological process in species ranging from insects to mammals. However, the function of JNKs in bacteria-induced intestinal inflammation is still poorly understood. In this study, a fish JNK (CiJNK) pathway was identified, and its potential roles in bacterial muramyl dipeptide (MDP)-induced intestinal inflammation were investigated in Ctenopharyngodon idella. The present CiJNK was found to possess a conserved dual phosphorylation motif (TPY) in a serine/threonine protein kinase (S_TKc) domain and to contain several potential immune-related transcription factor binding sites, including nuclear factor kappa B (NF-κB), activating protein 1 (AP-1), and signal transducer and activator of downstream transcription 3 (STAT3), in its 5′ flanking regions. Quantitative real-time PCR results revealed that the mRNA levels of the JNK pathway genes in the intestine were significantly upregulated after challenge with a bacterial pathogen (Aeromonas hydrophila) and MDP in a time-dependent manner. Additionally, the JNK pathway was found to be involved in regulating the MDP-induced expression levels of inflammatory cytokines (IL-6, IL-8, and TNF-α) in the intestine of grass carp. Moreover, the nutritional dipeptide carnosine and Ala–Gln could effectively alleviate MDP-induced intestinal inflammation by regulating the intestinal expression of JNK pathway genes and inflammatory cytokines in grass carp. Finally, fluorescence microscopy and dual-reporter assays indicated that CiJNK could associate with CiMKK4 and CiMKK7 involved in the regulation of the AP-1 signaling pathway. Overall, these results provide the first experimental demonstration that the JNK signaling pathway is involved in the intestinal immune response to MDP challenge in C. idella, which may provide new insight into the pathogenesis of inflammatory bowel disease.